Constructing Humanitarian-Based Law: A Philosophical Analysis of the Philanthropic Legal Paradigm - Novendri Mohamad Nggilu; Chami Yassine; Maya Khater (Faculty of Law, Universitas Sebelas Maret, 2025)
Positivist legal frameworks prioritize formal certainty over moral and social relevance, often failing to respond to global challenges such as inequality, environmental degradation, and digital exploitation. Philanthropic Law emerges as an alternative legal paradigm that emphasizes humanism, substantive justice, inclusion, and sustainability. This study aims to formulate the philosophical foundations and conceptual framework of Philanthropic Law as a response to technocratic approaches to law. Using a normative-juridical method combined with philosophical analysis, the research examines and reconstructs the nature, knowledge, and values of law from ontological, epistemological, and axiological perspectives. The findings indicate that Philanthropic Law integrates elements of natural law, utilitarianism, sociology of law, theories of justice, and progressive legal philosophy into a cohesive paradigm capable of addressing contemporary socio-legal challenges. This value-oriented approach supports the harmonization of international human rights norms within Indonesia’s constitutional framework and is consistent with Pancasila and the 1945 Constitution. The study proposes a reconceptualization of law as a participatory, adaptive, and justice-oriented process. It further recommends the adoption of value-based legislation, human rights–driven judicial reasoning, and transformative legal education to advance legal reform. Future study may explore the operationalization of Philanthropic Law in environmental, digital, and socio-economic regulatory frameworks.